Evaluation of the Implementation of the Islamic Religious Education Curriculum in Madrasah Ibtidaiyah Teacher Education in the Era of Independent Learning - Mardiah Astuti, Echa noviana; Echa noviana; Dita Tri Fitri; Mega Wati; Imelda Okta Diana (Universitas Muhammadiyah Palu, 2026)
This study aims to evaluate the implementation of the Islamic Religious Education Curriculum (PAI) in the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) in the era of Freedom of Learning. The background of this research departs from the demands for curriculum changes that emphasize flexibility, independence, and student-centered learning, so it is necessary to examine how it is implemented in the PGMI environment. The purpose of this study is to find out the extent to which the planning, implementation, and evaluation of PAI learning is in accordance with the principles of Independent Learning. The research method used is qualitative descriptive with data collection techniques through documentation, observation, and interviews with PAI lecturers and PGMI students. The results of the study show that the implementation of the PAI curriculum in the era of Independent Learning has increased in several aspects, especially in the use of more varied learning methods and encouraging active student participation. Project-based learning, group discussions, and the use of digital media are starting to be applied more consistently. However, this study also found obstacles in its implementation, such as limited supporting facilities, uneven digital literacy skills, and lack of lecturer training related to learning innovation. Learning evaluation also still tends to be oriented towards cognitive assessment so that it does not fully reflect the holistic character according to the principles of Freedom of Learning. Overall, the implementation of the PAI curriculum at PGMI is in the right direction, but it still needs optimization, especially in the aspects of media, strategy, and learning evaluation.